Kepemimpinan Transformasional dan Kebahagiaan di Tempat Kerja : Meta-Analisis - Desi Susianti; Hera Lestari Mikarsa; Dona Eka Putri; Moch. Iqbal (Observasi : Jurnal Publikasi Ilmu Psikologi, 2024)
This meta-analysis aims to measure the correlation between transformational leadership and workplace happiness by considering the effect size. The number of studies used in this study were 12 studies from 7 literatures that were considered to have met the requirements. The total sample of this study was 2662 people. The results of this meta-analysis indicate that a significant positive correlation between transformational leadership and workplace happiness is found at 95% CI (0.279; 0.612). The relationship between transformational leadership and workplace happiness is included in the moderate category with a score of r = 0.445. Similar results were found in other sample groups, namely the employee group (95% CI [0.234; 0.507]) with a score of r = 0.371. ; the health worker group obtained a score of r = 0.219 with 95% CI [0.142; 0.297]) and in the academic staff group a score of r = 0.565 with 95% CI [0.320; 0.808]). The results of the heterogeneity test showed good results and no publication bias.